Examining the health and wellbeing of women sanitation workers in Ghana and Kenya - Florence Dery; Elijah Bisung; Bernard Abudho; Ophelia Soliku; George Dery (Wellbeing, Space and Society, 2023)
About 3.6 billion people worldwide lack access to safely managed sanitation service. To bridge service gaps, informal sanitation businesses have emerged as alternative service providers to meet the sanitation needs of unserved populations. Informal sanitation workers include persons who empty septic tanks, clean toilets, sewers, and manage public toilets. They provide a fundamental public service particularly in areas where access to municipal sanitation service is limited. Through qualitative methodologies, this paper explores the lived experiences and associated health risks of women working in the informal sanitation sector in urban Ghana and Kenya. Our findings show that female informal sanitation workers were exposed to injuries and infections, stigma and discrimination, emotional and psychological distress, sexual harassment, and unhealthy coping strategies. Distinctively, younger female participants were more likely to experience sexual harassment. Because of social stigma, many of the women developed unsafe work practices such as refusal to wear PPE and working at night. By paying close attention to the embodied effects of informal sanitation work, we can better comprehend the daily politics, lived experiences, and urban social infrastructure regimes that have a significant impact on the quality of life of informal sanitation workers. The results are also crucial for developing programs for women's empowerment and labour and social protection policies, especially in lowincome settings where gender norms interact with income disparities and other sociopolitical issues to affect women's participation in the labor market.